WORKPLACE SPIRITUALITY PADA KARYAWAN PERBANKAN SYARIAH - Siswanto, Siswanto (Fakultas Ekonomi, UIN Maliki Malang, 2012)
The purpose of this study to describe workplace spirituality practices in Islamic banking according based on biographical characteristics. Total respondents in this study are 125 people. Biographical characteristics of respondents analyzed in this study include age, gender, marital status, and education. Data analysis was used analysis of variance (ANOVA) and Independent sample t-test. The results of this study indicate that workplace spirituality practices highly essential for Islamic banking employees.Â Therefore, manager of Islamic banking should incorporate human resource development programs to the needs of the nature of spirituality Â